Analytical modeling and performance study of GaAsNSb based single junction solar cell lattice matched to GaAs substrate for use in tandem solar cells. (December 2017) - Roy, D.; Samajdar, D.P.
Highlights: Mathematical modeling of non-linear I-V equation of a GaAsNSb based solar cell. Response of the Photovoltaic Module under the effect of irradiance and temperature. Calculation of Rs and Rp using an iterative computer simulation model. Essential parameters of Single Junction solar cell compared with experimental data. Abstract: A mathematical model based on MATLAB is first used to solve the coupled non-linear I-V equation of a single junction (SJ) solar cell using GaAsNSb quaternary alloy lattice matched to GaAs substrate. The response of the Photovoltaic (PV) Cell using series or parallel connection of two individual cells is investigated and the effect of variable irradiance and temperature conditions on the I-V and P-V characteristics of the cell is studied. The influence of series and parallel resistances Rs and Rp on the single diode model is calculated using an iterative computer simulation model. The experimental values of the essential parameters of the solar cell - short circuit current Isc, open-circuit voltage Voc, Fill factor (FF) and the efficiency of the SJ solar cell are used for calculating the optimized values of Rs and Rp to match the theoretically calculated output power with the experimental Maximum Power Point (MPP). The values of five different parameters Isc, Voc, Pmax, FF and η are compared using four different mathematical models under variable temperature and irradiance by including the effects of Rs and Rp .